Aspects regarding the quality of life in Roumanian rural space - Hurmuzache Tabita; Iancu Tiberiu; Fehér Andrea; Raicov Miroslav (2014)
The quality of life, is today an area of interest for the specialists of economic and political sciences. The interest in this field is given by the importance that is given to the human factor within the society. Thus, the evolution of the main indicators characterizing the quality of life is an important tool for monitoring the economic and social phenomena that occur within the society, providing an overview regarding the welfare of society. An important role in increasing the quality of life in rural area has the renovation and development of villages. In this respect a special attention should be paid to the modernization and expansion of basic rural infrastructure, resulting in the development of economic, social and cultural and even creating jobs, increasing employment degree of the population, thus increasing the revenue. Improved quality of life of Romanian inhabitants of the villages, determine, in equal measure, the economic development of rural areas. This, by the effects it produces causes increased income of the population, increased consumption of goods and services, resulting in a high satisfaction of demand, increase food security measures and therefore the quality of life. Development of entrepreneurship spirit of residents from rural area, increased accessibility degree to basic services and better capitalization of resources and traditional products are other measures which have as effect the improvement the standard of living of the rural population.
Keywords: Társadalomtudományok; Társadalom- és gazdaságföldrajz